Multiscale assessment of thermal comfort, exposure, inequality, and heat risk in Zhengzhou - Huina Zhang; Jun Zhang; Roman Fediuk; Ruoming Qi; Jia Xu; He Bai; Yingchu Guo (Scientific Reports)
Abstract Increasing thermal discomfort and thermal exposure threaten the health and well-being of urban residents. Existing research is usually limited to a single scale such as city-level and regional level. In addition, little has been reported on the differences in the inequality of population thermal exposure. In this paper, the Modified Temperature and Humidity Index (MTHI), population-weighted exposure model, and Gini coefficient (GINI) were applied to assess thermal comfort, thermal exposure, and inequality of thermal exposure at multiple scales (city-level, county-level, town-level and parcel-level) in Zhengzhou city from 1990 to 2020. Heat risks in the study area were assessed and risk categories of the assessment units were classified. The results showed that in the past three decades, the thermal comfort of residents had gradually decreased, and the degree of thermal exposure had steadily increased. Thermal exposure inequality coefficients showed complex variations at different scales and regions. The assessment of multi-scale administrative districts had a significant scale effect, indicating that the finer the spatial scale, the stronger the heterogeneity. In 2020, 27 towns had thermal discomfort; 24 towns were characterized by high thermal exposure; and 24 towns had inequality in thermal exposure. 305 parcels had thermal discomfort; 239 parcels were characterized by high thermal exposure; and 64 parcels had inequality in thermal exposure. The heat risk assessment showed that the towns with lower heat risk were mainly located in the central and northern areas of Zhengzhou. The heat risk values of the parcels in the urban center area were polarized. The heat risk categories were dominated by thermal comfort-low exposure-low inequality and thermal discomfort-high exposure-low inequality. This research could lead to a better understanding of thermal exposure and thermal exposure inequality at multiple scales, contributing to improved environmental justice and sustainable urban development.